Down in the valley a writer's landscape - Lee, Laurie 1914-1997 (Penguin modern classics, 2020)
"'Before I left the valley I thought everywhere was like this. Then I went away for 40 years and when I came back I realized that nowhere was like this.' Laurie Lee walked out of his childhood village one summer morning to travel the world, but he was always drawn back to his beloved Slad Valley, eventually returning to make it his home. In this portrait of his Cotswold home, Laurie Lee guides us through its landscapes, and shares memories of his village youth - from his favourite pub to winter skating on the pond, the church through the seasons, local legends, learning the violin and playing jazz records in the privy on a wind-up gramophone. Filled with wry humour and a love of place, "Down in the Valley" is a writer's tribute to the landscape that shaped him, and where he found peace."